Experimental Study on Mechanical Properties and Pore Structure Deterioration of Concrete under Freeze–Thaw Cycles - Kai Zhang (MDPI AG, 2021)
Understanding the evolution of mechanical properties and microscopic pore structure of concrete after freeze–thaw cycles is essential to assess the durability and safety of concrete structures. In this work, the degradation law of mechanical properties and damage characteristic of micro-structure of concrete with two water-cement ratios (w/c = 0.45 and 0.55) is investigated under the condition of freezing–thawing cycles. The influence of loading strain rate on dynamic compressive strength is studied. The microscopic pore structure after frost damage is measured by low-field nuclear magnetic resonance (LF-NMR) technique. Then, a damage model based on the porosity variation is established to quantitatively describe the degradation law of macroscopic mechanical properties. The test results show that the relative dynamic modulus of elasticity (RDME), dynamic compressive strength, flexural strength, and splitting tensile strength of concrete decrease with the increase of freeze–thaw cycles. Empirical relations of concrete dynamic increase factor (DIF) under the action of freeze–thaw cycles are proposed. Moreover, the experimental results of NMR indicate that the porosity as well as the proportion of meso-pores and macro-pores of concrete gradually increased with the increasing of freeze–thaw cycles. The research results can provide reference and experimental support for the anti-frost design theory and durability life prediction of hydraulic concrete structures in cold regions.